Pengembangan Keterampilan Pengelasan Kelompok Usaha CV Bahrur Ulum Karya Teknik, Serang, Banten - Rosidi; Budi Yuwono; Nugroho Eko (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2024)
This community service is a program for applying appropriate technology to CV Panancangan service partners which aims to develop a welding workshop and engineering workshop business unit which is engaged in making hospital equipment, located in Panancangan Village, Serang City. The problem currently faced by service partners who are engaged in the field of hospital equipment manufacturing services, where the welding process still uses SMAW welding and GTAW welding, so that the results of welding service products still contain many weld defects produced and the production process is less efficient. This welding defect often appears when welding thin plates, especially when welding is carried out completely or continuously. The solution that has been provided is to manufacture and provide grants for Seam Welding machines with small energy input specifications so that they can be used by Small and Medium Industries. Seam Welding applications are still very minimal, only limited to large industrial scales. The method used is using a welding transformer with 1 phase electrical input and 5 kVA output, so that it can be used in Small and Medium Industries which mostly use 1 phase electricity. This Seam Welding machine is designed to be able to adjust the voltage and amperage output according to needs. The rotation of the electrode wheel is driven using a drive motor with a rotational rpm setting.